EFFECTIVENESS OF GAPOKTAN AS FORMAL FARMER GROUP IN SUPPORTING SUSTAINABLE RICE FARMING - Huanza, M; Sari, Yulia; Putri, Trisna Wahyu Swasdiningrum; Amalina, Dian (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
The effectiveness of farmer group institutions (Gapoktan) plays a critical role in enhancing the resilience and sustainability of rice farming systems. This birutoto study aims to examine the key factors influencing farmers’ adoption of sustainable farming practices, evaluate the institutional effectiveness of farmer groups (Gapoktan), and examine the relationship between institutional effectiveness and the implementation of sustainable agricultural practices among rice farmers. The research was conducted from March to May 2025 using a purposive sampling method involving 30 rice farmers as respondents. Data were collected through surveys using structured questionnaires and analyzed using descriptive, correlation (Spearman Rank), and binary logit methods. The results show that enthusiasm and responsibility of the farmer group leader in the process of implementing sustainable agriculture have a statistically significant effect. Findings reveal that Gapoktan in Ulak Petangisan plays a significant role not only in facilitating the distribution of production inputs but also in fostering communication, collaboration, and knowledge-sharing among farmers. However, institutional performance remains suboptimal, with most indicators categorized as moderately effective, and some aspects such as marketing support and price stabilization classified as less effective. There is a significant relationship between the institutional effectiveness of farmer groups (Gapoktan) and the adoption of sustainable agricultural practices. The study highlights the need for strengthening institutional capacity in strategic areas to enhance the transition toward sustainable agriculture.